Assessment of a rapid diagnostic test based on loop-mediated isothermal amplification (LAMP) to identify the most frequent pathogens causing hospital-acquired pneumonia - Sellarès-Crous, Anna; Martínez-Trejo, Arturo; Arnalda-Muñoz, Natàlia; Gatti, Giulia; Villanueva-López, Miriam; Vergara-Gómez, Andrea; Marco-Reverté, Francesc; Espasa-Soley, Mateu; Vila-Estapé, Jordi (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionHospital-acquired pneumonia (HAP) is a serious infection affecting patients in the hospital setting. This study aimed to evaluate a novel multiplex detection method using loop-mediated isothermal amplification (LAMP) technology to identify six primary bacterial pathogens responsible for HAP directly from respiratory samples.MethodsA total of 119 clinical samples were analyzed by LAMP technology, including mainly bronchoalveolar lavages, endotracheal aspirates, and bronchoaspirates.Results and discussionThe results of the LAMP and traditional culture methods showed an accuracy of 93.0%. In some discordant cases between culture and LAMP, multiplex PCR (FilmArray Pneumonia Panel) showed a strong correlation with the LAMP results, confirming the potential use of this technique as a diagnostic detection tool. The clinical sensitivity of the LAMP assay was 93.3% with a specificity of 92.0%. Correlation analysis revealed a weak negative relationship between bacterial load and time to positivity (r = −0.177, p = 0.05). This study underscores the potential of LAMP as a rapid and accurate tool for the diagnosis of HAP, facilitating the turnaround time for microbiology laboratory results, which is critical for improving the outcomes of patients with HAP.